Efforts to conserve endangered terrestrial orchids in situ and ex situ at two natural reserves within Central Mexico - Rangel-Villafranco, Mónica; Ortega-Larrocea, Pilar (Lankesteriana: International Journal on Orchidology, 2015)
The natural vegetation in and around Mexico City once harbored an unusually high number of plant and animal (insect) species, including endemics (Vázquez 1973, Ceballos & Galindo 1984, Rzedowski 1991). The high diversity in this region has been attributed to the unusual topography resulting from a series of volcanic eruptions that ended ca. 1800 years ago (Siebe et al. 2004). In addition, two phyto-geographic regions overlap within Central Mexico that support diverse vegetation types (e.g., shrubs, mature pine forests).